RET gene fusion and emergent Selpercatinib resistance in a calcitonin-rich neuroendocrine carcinoma: a case report - Pishdad, Reza; Illei, Peter B.; Gocke, Christopher D.; Ball, Douglas W. (Frontiers in Oncology, 2024)
Metastatic lung neuroendocrine carcinomas provide diagnostic challenges in identifying the cell of origin. High level calcitonin expression is not pathognomonic for medullary thyroid cancer. Tumor mutation analysis may provide essential clues regarding tissue origin and treatment targets. Oncogenic RET gene fusions have been identified in non-small cell lung cancer and non-medullary thyroid cancers, whereas RET point mutations are the key genetic finding in both inherited and sporadic MTC. Patients who receive radiation for the treatment of other cancers have an increased risk of developing a second malignancy, including a neuroendocrine carcinoma. Herein, we present a case of calcitonin-rich neuroendocrine carcinoma emerging on a background of prior radiation and chemotherapy for the treatment of Hodgkin’s disease. Identification of a RET gene rearrangement (KIF5B-RET) led to initial successful treatment with selpercatinib, with eventual resistance associated with an activating mutation involving the MEK1 protein (MAP2K1 p. E102-I103 del) that led to relapse and progression of the disease.